Automatic morphological characterization of nanobubbles with a novel image segmentation method and its application in the study of nanobubble coalescence - Wang, Yuliang; Wang, Huimin; Bi, Shusheng; Guo, Bin (Beilstein Journal of Nanotechnology, 2015)
Nanobubbles (NBs) on hydrophobic surfaces in aqueous solvents have shown great potential in numerous applications. In this study, the morphological characterization of NBs in AFM images was carried out with the assistance of a novel image segmentation method. The method combines the classical threshold method and a modified, active contour method to achieve optimized image segmentation. The image segmentation results obtained with the classical threshold method and the proposed, modified method were compared. With the modified method, the diameter, contact angle, and radius of curvature were automatically measured for all NBs in AFM images. The influence of the selection of the threshold value on the segmentation result was discussed. Moreover, the morphological change in the NBs was studied in terms of density, covered area, and volume occurring during coalescence under external disturbance.
Keywords: atomic force microscopy; characterization; coalescence; nanobubbles; segmentation

(untitled) - Lou, S.-T.; Ouyang, Z.-Q.; Zhang, Y.; Li, X.-J.; Hu, J.; Li, M.-Q.; Yang, F.-J. (J. Vac. Sci. Technol., B, 2000)

(untitled) - Yang, S.; Dammer, S. M.; Bremond, N.; Zandvliet, H. J. W.; Kooij, E. S.; Lohse, D. (Langmuir, 2007)

(untitled) - Tyrrell, J. W. G.; Attard, P. (Phys. Rev. Lett., 2001)

(untitled) - Agrawal, A.; Park, J.; Ryu, D. Y.; Hammond, P. T.; Russell, T. P.; McKinley, G. H. (Nano Lett., 2005)

(untitled) - Holmberg, M.; Kühle, A.; Garnæs, J.; Mørch, K. A.; Boisen, A. (Langmuir, 2003)

(untitled) - Bhushan, B.; Wang, Y.; Maali, A. (J. Phys.: Condens. Matter, 2008)

(untitled) - Tyrrell, J. W. G.; Attard, P. (Langmuir, 2002)

(untitled) - Wang, Y.; Bhushan, B.; Zhao, X. (Nanotechnology, 2009)

(untitled) - Wang, Y.; Bhushan, B.; Zhao, X. (Langmuir, 2009)

(untitled) - Switkes, M.; Ruberti, J. W. (Appl. Phys. Lett., 2004)

(untitled) - Steitz, R.; Gutberlet, T.; Hauss, T.; Klösgen, B.; Krastev, R.; Schemmel, S.; Simonsen, A. C.; Findenegg, G. H. (Langmuir, 2003)

(untitled) - Poynor, A.; Hong, L.; Robinson, I. K.; Granick, S.; Zhang, Z.; Fenter, P. A. (Phys. Rev. Lett., 2006)

(untitled) - Zhang, X. H.; Quinn, A.; Ducker, W. A. (Langmuir, 2008)

(untitled) - Chan, C. U.; Ohl, C.-D. (Phys. Rev. Lett., 2012)

(untitled) - Karpitschka, S.; Dietrich, E.; Seddon, J. R. T.; Zandvliet, H. J. W.; Lohse, D.; Riegler, H. (Phys. Rev. Lett., 2012)

(untitled) - Xing, Z.; Wang, J.; Ke, H.; Zhao, B.; Yue, X.; Dai, Z.; Liu, J. (Nanotechnology, 2010)

(untitled) - Yin, T.; Wang, P.; Zheng, R.; Zheng, B.; Cheng, D.; Zhang, X.; Shuai, X. (Int. J. Nanomed., 2012)

(untitled) - Weber, J.; Agblevor, F. A. (Process Biochem., 2005)

(untitled) - Ishida, N.; Sakamoto, M.; Miyahara, M.; Higashitani, K. (J. Colloid Interface Sci., 2002)

(untitled) - Palmer, L. A.; Cookson, D.; Lamb, R. N. (Langmuir, 2011)

(untitled) - Hampton, M. A.; Nguyen, A. V. (Adv. Colloid Interface Sci., 2010)

(untitled) - Joseph, P.; Cottin-Bizonne, C.; Benoît, J. M.; Ybert, C.; Journet, C.; Tabeling, P.; Bocquet, L. (Phys. Rev. Lett., 2006)

(untitled) - Lauga, E.; Stone, H. A. (J. Fluid Mech., 2003)

(untitled) - Ou, J.; Perot, B.; Rothstein, J. P. (Phys. Fluids, 2004)

(untitled) - Sbragaglia, M.; Prosperetti, A. (J. Fluid Mech., 2007)

(untitled) - Wang, Y.; Bhushan, B.; Maali, A. (J. Vac. Sci. Technol., A, 2009)

(untitled) - Bhushan, B.; Wang, Y.; Maali, A. (Langmuir, 2009)

(untitled) - Janda, P.; Frank, O.; Bastl, Z.; Klementová, M.; Tarábkova, H.; Kavan, L. (Nanotechnology, 2010)

(untitled) - Alsawafta, M.; Badilescu, S.; Truong, V.-V.; Packirisamy, M. (Nanotechnology, 2012)

(untitled) - Zhang, X. H.; Zhang, X. D.; Lou, S. T.; Zhang, Z. X.; Sun, J. L.; Hu, J. (Langmuir, 2004)

(untitled) - Guan, M.; Guo, W.; Gao, L.; Tang, Y.; Hu, J.; Dong, Y. (ChemPhysChem, 2012)

(untitled) - Berkelaar, R. P.; Seddon, J. R. T.; Zandvliet, H. J. W.; Lohse, D. (ChemPhysChem, 2012)

(untitled) - Bhushan, B.; Pan, Y.; Daniels, S. (J. Colloid Interface Sci., 2013)

(untitled) - Belova, V.; Krasowska, M.; Wang, D.; Ralston, J.; Shchukin, D. G.; Möhwald, H. (Chem. Sci., 2013)

(untitled) - van Limbeek, M. A. J.; Seddon, J. R. T. (Langmuir, 2011)

(untitled) - Zhang, X.; Uddin, M. H.; Yang, H.; Toikka, G.; Ducker, W.; Maeda, N. (Langmuir, 2012)

(untitled) - Lüderitz, L. A. C.; von Klitzing, R. (Langmuir, 2012)

(untitled) - Zhang, X.; Chan, D. Y. C.; Wang, D.; Maeda, N. (Langmuir, 2013)

(untitled) - Walczyk, W.; Schön, P. M.; Schönherr, H. (J. Phys.: Condens. Matter, 2013)

(untitled) - Guo, W.; Shan, H.; Guan, M.; Gao, L.; Liu, M.; Dong, Y. (Surf. Sci., 2012)

(untitled) - Kass, M.; Witkin, A.; Terzopoulos, D. (Int. J. Comput. Vision, 1988)

(untitled) - Wang, Y.; Wang, H.; Bi, S. (AIP Adv., 2014)

(untitled) - Song, B.; Walczyk, W.; Schönherr, H. (Langmuir, 2011)

(untitled) - Yang, J.; Duan, J.; Fornasiero, D.; Ralston, J. (J. Phys. Chem. B, 2003)

(untitled) - Kameda, N.; Sogoshi, N.; Nakabayashi, S. (Surf. Sci., 2008)

(untitled) - Borkent, B. M.; de Beer, S.; Mugele, F.; Lohse, D. (Langmuir, 2010)

Intermolecular & Surface Forces - Israelachvili, J. (Academic Press, 1992)

(untitled) - Li, D.; Jing, D.; Pan, Y.; Wang, W.; Zhao, X. (Langmuir, 2014)

(untitled) - Lu, Y.-H.; Yang, C.-W.; Hwang, I.-S. (Langmuir, 2012)

(untitled) - Brenner, M. P.; Lohse, D. (Phys. Rev. Lett., 2008)